The WTO rules versus multilateral environmental agreements: the search for reconciliation - Hamid, Abdul Ghafur@Khin Maung Sein; Nik Mahmod, Nik Ahmad Kamal (Centre for International & Environmental Law, Macquarie Law School, Macquarie University, NSW 2109, Australia, 2008)
The debate over free trade and protection of the environment has been on the table of the WTO since its very inception. In 2001, the Doha Development Agenda initiated a set of negotiations on the relationship between the WTO and MEAs. However, the negotiations have so far failed to yield any tangible result. This paper examines the adequacy of the environmental exceptions to WTO rules. Environmentally related disputes decided by the WTO Panel or Appellate Body are analysed to determine whether the rulings are one-sided and if trade rules are given preference over environmental concerns. The paper focuses on how to address the issue of the relationship between the WTO rules and MEAs in light of relevant principles of international law. The paper concludes with suggestions for improvement in the legal rules and dispute resolution.